Optimizing Quality of Life Through an Adaptive Biophilic Architecture Sensory Approach - Gaizka Royhan Astawa; Andarita Rolalisasi; Febby Rahmatullah Masruchin (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Massive urbanization has created the phenomenon of "urban-nature disconnect," where city dwellers spend over 90% of their time indoors, shielded from natural elements (Kellert, 2008). This condition negatively impacts mental and physical health, often referred to as nature deficit disorder. Biophilic architecture emerged as a design solution aimed at reconnecting humans with nature through the built environment (Wilson, 1984). However, many current biophilic applications remain focused on purely cosmetic visual aspects, such as the placement of ornamental plants, without considering deeper sensory experiences. Juhani Pallasmaa (2005), in his theory of "The Eyes of the Skin," emphasizes that architecture should engage all human senses to create a sense of "presence" and a holistic sense of well-being. Therefore, a sensory approach is needed that is not merely statistical but also adaptive to environmental changes to optimize the quality of life of its occupants. The purpose of this research is to formulate biophilic design parameters that incorporate the senses of touch, smell, and hearing as adaptive elements in buildings. The contribution of this research is expected to be a guide for architects in designing spaces that support circadian health and human psychological comfort through dynamic natural stimulation.